2001
DOI: 10.1023/a:1005615932694
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this work was to investigate whether ethylene is involved in the oxidative and defensive responses of barley to the aphids Schizaphis graminum (biotype C) and Rhopalophum padi. The effect of aphid infestation on ethylene production was measured in two barley cultivars (Frontera and Aramir) that differ in their susceptibility to aphids. Ethylene evolution was higher in plants infested for 16 hr than in plants infested for 4 hr in both cultivars. Under aphid infestation, the production of ethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(36 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Crude enzyme preparation for superoxide dismutase (SOD) and peroxidase (POD) assays involved tissue homogenization in 5 ml of 100 mM potassium phosphate buffer (pH 7.0) following the procedure of He et al [36]. Assays used for POD, SOD, and catalase (CAT) were those described by Argandona et al [37] and Yin et al [38]. Soluble sugar (SS) content was determined using anthrone colorimetry as described by Li [39], and malondialdehyde (MDA) content was measured by the thiobarbituric acid method according to Deng et al [40].…”
Section: Methodsmentioning
confidence: 99%
“…Crude enzyme preparation for superoxide dismutase (SOD) and peroxidase (POD) assays involved tissue homogenization in 5 ml of 100 mM potassium phosphate buffer (pH 7.0) following the procedure of He et al [36]. Assays used for POD, SOD, and catalase (CAT) were those described by Argandona et al [37] and Yin et al [38]. Soluble sugar (SS) content was determined using anthrone colorimetry as described by Li [39], and malondialdehyde (MDA) content was measured by the thiobarbituric acid method according to Deng et al [40].…”
Section: Methodsmentioning
confidence: 99%
“…35,141 Induction of H 2 O 2 has been studied in oat, wheat, barley and groundnut against D. noxia, R. padi, Schizaphis graminum Rond., H. armigera and S. litura. 4,5,132,139 Argandona et al 144 observed induction of H 2 O 2 in barley infested with S. graminum after 20 min of infestation, indicating that H 2 O 2 could be the beginning of a cascade of physiological and molecular events leading to production of further defensive components, and protection of plants from subsequent damage. ROS mediate the defensive gene activation and establish additional defenses by regulating the transcription and/or by interacting with other signal components like phosphorylation in plant systems in response to a variety of stresses.…”
Section: Future Outlookmentioning
confidence: 99%
“…For example, increases in ethylene production was observed in tomato infested with potato aphid, alfalfa infested with Therioaphis maculate (spotted alfalfa aphid), wheat infested with Schizaphis graminum (greenbug), and barley infested with Rhopalosiphum padi (oat aphid) and Russian wheat aphid (Dillwith et al, 1991; Anderson and Peters, 1994; Miller et al, 1994; Argandoña et al, 2001; Mantelin et al, 2009). Changes in expression of genes putatively involved in ethylene metabolism/signaling also have been observed in melon plants responding to the melon and cotton aphid infestation, in tomato infested with the potato aphid, and Arabidopsis infested with the GPA (Moran et al, 2002; Anstead et al, 2010; Mantelin et al, 2009).…”
Section: The Arabidopsis Thaliana-green Peach Aphid Pathosystem: a Momentioning
confidence: 99%